Differences in Contractile Function of Myofibrils within Human Embryonic Stem Cell-Derived Cardiomyocytes vs. Adult Ventricular Myofibrils Are Related to Distinct Sarcomeric Protein Isoforms - Iorga, Bogdan; Schwanke, Kristin; Weber, Natalie; Wendland, Meike; Greten, Stephan; Piep, Birgit; dos Remedios, Cristobal G.; Martin, Ulrich; Zweigerdt, Robert; Kraft, Theresia; Brenner, Bernhard (Frontiers in Physiology, 2018)
Characterizing the contractile function of human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) is key for advancing their utility for cellular disease models, promoting cell based heart repair, or developing novel pharmacological interventions targeting cardiac diseases. The aim of the present study was to understand whether steady-state and kinetic force parameters of β-myosin heavy chain (βMyHC) isoform-expressing myofibrils within human embryonic stem cell-derived cardiomyocytes (hESC-CMs) differentiated in vitro resemble those of human ventricular myofibrils (hvMFs) isolated from adult donor hearts. Contractile parameters were determined using the same micromechanical method and experimental conditions for both types of myofibrils. We identified isoforms and phosphorylation of main sarcomeric proteins involved in the modulation of force generation of both, chemically demembranated hESC-CMs (d-hESC-CMs) and hvMFs. Our results indicate that at saturating Ca2+ concentration, both human-derived contractile systems developed forces with similar rate constants (0.66s-1 and 0.68s-1), reaching maximum isometric force that was significantly smaller for d-hESC-CMs (42kPa) than for hvMFs (94kPa). At submaximal Ca2+-activation, where intact cardiomyocytes normally operate, contractile parameters of d-hESC-CMs and hvMFs exhibited differences. Ca2+ sensitivity of force was higher for d-hESC-CMs (pCa50=6.04) than for hvMFs (pCa50=5.80). At half-maximum activation, the rate constant for force redevelopment was significantly faster for d-hESC-CMs (0.51s-1) than for hvMFs (0.28s-1). During myofibril relaxation, kinetics of the slow force decay phase were significantly faster for d-hESC-CMs (0.26s-1) than for hvMFs (0.21s-1), while kinetics of the fast force decay were similar and 20x faster. Protein analysis revealed that hESC-CMs had essentially no cardiac troponin-I, and partially non-ventricular isoforms of some other sarcomeric proteins, explaining the functional discrepancies. The sarcomeric protein isoform pattern of hESC-CMs had features of human cardiomyocytes at an early developmental stage. The study indicates that morphological and ultrastructural maturation of βMyHC isoform-expressing hESC-CMs is not necessarily accompanied by ventricular-like expression of all sarcomeric proteins. Our data suggest that hPSC-CMs could provide useful tools for investigating inherited cardiac diseases affecting contractile function during early developmental stages.